3143 DIAMOND: A Digital Platform for Workforce Development. (27th March 2019) - Eakin, Brenda; Samuels, Elias M.; Ellingrod, Vicki; Jones, Carolynn; Martina, Camille Anne; Peyre, Sarah; Rushforth, Alice M; Chung, Haejung; Perorazio, Thomas E
Abstract : OBJECTIVES/SPECIFIC AIMS: The DIAMOND project encourages study team workforce development through the creation of a digital learning space that brings together resources from across the CTSA consortium. This allows for widespread access to and dissemination of training and assessment materials. DIAMOND also includes access to an ePortfolio that encourages CRPs to define career goals and document professional skills and training. METHODS/STUDY POPULATION: Four CTSA institutions (the University of Michigan, the Ohio State University, University of Rochester, and Tufts CTSI) collaborated to develop and implement the DIAMOND portal. The platform is structured around eight competency domains, making it easy for users to search for research training and assessment materials. Contributors can upload links to (and meta-data about) training and assessment materials from their institutions, allowing resources to be widely disseminated through the DIAMOND platform. Detailed information about materials included in DIAMOND is collected through an easy to use submission form. DIAMOND also includes an ePortfolio designed for CRPs. This encourages workforce development by providing a tool for self-assessment of clinical research skills, allowing users to showcase evidence of experience, training and education, and fosters professional connections. RESULTS/ANTICIPATED RESULTS: To date, more than 100 items have been posted to DIAMOND from nine contributors. In the first 30 days there were 229 active users with more than 500 page views from across the U.S. as well as China and India. Training materials were viewed most often from four competency domains: 1) Scientific Concepts & Research Design, 2) Clinical Study Operations, 3) Ethical & Participant Safety, and 4) Leadership & Professionalism. Additionally, over 100 CRPs have created a DIAMOND ePortfolio account, using the platform to document skills, connect with each other, and search for internships and job opportunities. DISCUSSION/SIGNIFICANCE OF IMPACT: Lessons learned during development of the DIAMOND digital platform include defining relevant information to collect for the best user experience; selection of a standardized, user-friendly digital platform; and integration of the digital network and ePortfolio. Combined, the DIAMOND portal and ePortfolio provide a professional development platform for clinical research professionals to contribute, access, and benefit from training and assessment opportunities relevant to workforce development and their individual career development needs.